Efter sista ridån : handlingar som uppstår och bevaras på svenska institutionsteatrar - Bergvall,Linnea (2023)
Theatre and archives have existed as parallel institutions for centuries, yet not much focus has historically been put on studying the function of archives within the theatrical institution. This thesis aims to examine the use and method of archives within Swedish institutional theatres by looking at the material that is created and used during a stage production at a Swedish institutional theatre, what happens with the material once the production is finished, as well as the institutions’ view on their own role in the archival process. Informants from three different, Swedish institutional theatres were questioned about their respective institutions’ archival practices through a deep interview, all three assigned archival work for their theatre, to varying degrees and titles. The work of the theatres was then put into the perspective of new institutional organisation theory to assuage whether the methods of the different institutions fall within the scope of isomorphism, as posed by Paul DiMaggio and Walter W. Powell. The study finds that though there are indeed similarities between the institutions, the methods with which the institutions conduct their archival work differs slightly. When applying the theory of isomorphism, the results suggest that while full isomorphism has not occurred, it is very possible that the institutions are heading towards it. While some of the institutions have faced external pressure to work on their archival routines, there is no general consensus or government decision on how institutional theatres specifically are supposed to conduct their archival work.
Keywords: Archival science; archives; new institutional organisation theory; theatre; Process-oriented archival description; Arkivvetenskap; arkiv; institutionsteater; nyinstitutionell teori; organisationsteori; teater; verksamhetsbaserad arkivredovisning